1996
DOI: 10.4141/cjas96-021
|View full text |Cite
|
Sign up to set email alerts
|

Carcass and organoleptic characteristics of meat from steers grazed on alfalfa/grass pastures and finished on grain

Abstract: Numerous studies over the past 20 yr have examined the relationship between forage-finishing and beef quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
19
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 2 publications
6
19
0
1
Order By: Relevance
“…The meat tenderness of the two types of animals, after correction by taking into account these 2 factors, were not significantly different. These results confirm those of other authors [13,32,67]. However, when hay-finished bulls were compared to grass silage-finished bulls, at the same amount of energy intake, hay-finished bulls had lower growth rates and carcass fatness degrees [61].…”
Section: Variations Of Diet Compositionsupporting
confidence: 82%
See 1 more Smart Citation
“…The meat tenderness of the two types of animals, after correction by taking into account these 2 factors, were not significantly different. These results confirm those of other authors [13,32,67]. However, when hay-finished bulls were compared to grass silage-finished bulls, at the same amount of energy intake, hay-finished bulls had lower growth rates and carcass fatness degrees [61].…”
Section: Variations Of Diet Compositionsupporting
confidence: 82%
“…The pigmentation and the capillary density of the restricted bulls were also higher. The rib cut colour of steers slaughtered directly from pasture feeding was judged darker than that of control steers fed subsequently a finishing feeding with a high cereal content [67]. The longer was the finishing period,…”
Section: The Feeding Level Before Slaughtermentioning
confidence: 93%
“…However, Cerdeno et al (2005) indicated that it was possible to improve the sensory qualities of beef from grass based systems, by allowing a finishing period on concentrate diets, while at the same time retaining the advantages of grass feeding. Similarly, studies on steers and dairy bulls by McCaughey and Cliplef (1996) and Vestergaard et al (2000), respectively, showed that animals raised on grass and finished on concentrate diets for two to three months produced beef with similar desirable sensory quality to intensively fed animals.…”
Section: Introductionmentioning
confidence: 90%
“…To illustrate this we have compared the data of McCaughey and Clipfel (1996) with predictions from GrassGro. McCaughey and Clipfel (1996) took the steers from the trial reported by Popp et al (1997a,b) after removal from the pastures in 1993 and re-randomized them into three equal groups. Group 1 was slaughtered immediately following removal from pasture.…”
Section: Extrapolationsmentioning
confidence: 99%
“…The remaining steers were placed in a feedlot and fed for either 33 d (Group 2) or 75 d (Group 3) on a ration of 50:50 barley:brome/alfalfa hay for 33 d rising to 75:25 barley:hay on day 34 for Group 3 steers. We have simulated this study in GrassGro, using default values for the characteristics of barley and of good quality grass/alfalfa hay (Table 1), and compared the final liveweights measured by McCaughey and Clipfel (1996) with GrassGro predictions. We did not consider the 1991 data because of the late start to the grazing season due to unavailability of steers and the hay cut that was taken prior to the steers being placed on pasture.…”
Section: Extrapolationsmentioning
confidence: 99%